Effectiveness of the Constructivist Approach (Guided Inquiry) in Chemistry Learning: A Systematic Review - Pahriah, Pahriah; Adnyana, Putu Budi; Ariawan, I Putu Wisna; Wesnawa, I Gede Astra (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study aims to identify the effectiveness of the Guided Inquiry approach in enhancing critical thinking skills, learning motivation, conceptual understanding, and student learning outcomes in chemistry education. Utilizing the Systematic Literature Review (SLR) method, this research reviews various relevant studies from international and national databases such as Scopus, ERIC, and SINTA, employing focused keywords. The analyzed articles were selected based on inclusion criteria that encompassed topic relevance and the availability of empirical data, resulting in 27 final articles for further analysis. The qualitative analysis results indicate that Guided Inquiry not only improves students' conceptual understanding of chemistry concepts but also strengthens critical thinking skills and learning motivation. Quantitative findings demonstrate a pattern of increased effectiveness across various educational levels, with more significant results observed at the secondary education level compared to higher education. Several factors, such as the role of teacher facilitation and student readiness, were also identified as important influences on the success of this approach. This study recommends the integration of the Guided Inquiry approach into the chemistry education curriculum, accompanied by the development of technology-based modules and continuous training for educators, to maximize the potential for constructive learning.